Earnings Targets and Annual Bonus Incentives - Indjejikian, Raffi J.; Matějka, Michal; Merchant, Kenneth A.; Van der Stede, Wim A. (The Accounting Review, 2014)
ABSTRACT: We examine the extent to which firms use past performance as a basis for setting earnings targets in their bonus plans and assess the implications of such targets for managerial incentives. We find that high-profitability firms commonly decrease earnings targets when their managers fail to meet prior-year targets but rarely increase targets. Conversely, we find that low-profitability firms commonly increase earnings targets when their managers meet or exceed prior-year targets but rarely decrease targets. This target-revision process yields a serial correlation in target difficulty—targets remain relatively easy (or difficult) through time. We also find that firms are reluctant to revise earnings targets below zero, resulting in an unusually high frequency of zero earnings targets that are abnormally difficult to achieve. Collectively, our findings suggest that firms incorporate past performance information into targets, yet they do so only to a limited extent. This is consistent with theoretical arguments that highlight the benefits of contractual commitments. Data Availability: Data used in this study cannot be made public due to the confidentiality agreement with the sponsoring organization.